QEEG correlates of cognitive processing speed in children and adolescents with traumatic brain injuries. Issue 3 (3rd July 2021) - Ferraracci, Joseph; Anzalone, Christopher; Bridges, Rachel M.; Moore, R. Davis; Decker, Scott L.
Abstract: Both quantitative electroencephalography (qEEG) and cognitive measures have been used to understand the underlying brain changes that occur in individuals after experiencing a traumatic brain injury, however, research exploring the relationship between qEEG patterns and cognitive test performance is scarcely studied in school-aged populations. The purpose of the present study was to explore first, the neuropsychological and academic deficits in young individuals with TBI; and second, the underlying relationship between qEEG patterns and cognitive test performance. Analyses included 21 school-aged participants whom have experienced a recent TBI and 15 school-aged participants whom have never experienced a TBI. Mean subtest and composite scores were compared and regression analyses were used to determine whether alpha band and beta band qEEG coherence values predicted processing speed measures. Results suggest that young individuals who experienced a recent TBI exhibit general deficits in cognition and academic skills beyond what would be expected in the general population. Further, beta band coherence with the frontal brain regions significantly predicted processing speed scores, providing evidence of a relationship between qEEG patterns and processing speed. This outlines a relatively inexpensive method for utilizing neural connectivity to verify cognitive deficits for school-aged individuals with a recent TBI.